2017
DOI: 10.1049/iet-smt.2016.0369
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of severity of voltage flicker caused by second harmonic

Abstract: Second harmonic produces asymmetrical waveform which leads to fluctuation of root-meanssquare (rms) value with certain frequency. Meanwhile, function of weighting filter in flickermeter is designed for sixth-order low-pass filtering function with frequency to be limited to 35 Hz, signal with frequency ranging from 35 to 100 Hz, at certain gain, still can pass through. Since the second harmonic produces fluctuation of rms value with 50 Hz, there is high possibility that it can be passed by this filter and thus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 32 publications
(39 reference statements)
0
12
0
Order By: Relevance
“…2 c , the amplitude of the second‐order harmonic current depends on the difference between C1 and C2. According to [30–32], the tolerance of an aluminium electrolytic capacitor is practically determined as ±20% from its specified value. In the worst‐case investigation in this paper, a 40% difference is considered; consequently, the IEEE 1547 standard is not satisfied because of the excessive second‐order harmonic current.…”
Section: Harmonic Currents Of Dshbmmentioning
confidence: 99%
See 1 more Smart Citation
“…2 c , the amplitude of the second‐order harmonic current depends on the difference between C1 and C2. According to [30–32], the tolerance of an aluminium electrolytic capacitor is practically determined as ±20% from its specified value. In the worst‐case investigation in this paper, a 40% difference is considered; consequently, the IEEE 1547 standard is not satisfied because of the excessive second‐order harmonic current.…”
Section: Harmonic Currents Of Dshbmmentioning
confidence: 99%
“…Additionally, based on half-bridge topology, the inequality between the average voltage values across the two dc-link capacitors or the difference between the two capacitances [5] causes a line frequency ripple voltage on the dc-link, resulting in the appearance of a second-order harmonic current. This grid-injected second-order harmonic current causes asymmetrical sinusoidal voltage waveforms in electrical power systems [26][27][28][29] as well as a voltage flicker [30]. These phenomena have undesirable effects on the electrical load in an electrical system, such as core losses in electrical machines or the saturation of an inductor or transformer.…”
Section: Introductionmentioning
confidence: 99%
“…The measurement of harmonic usually uses harmonic analyzer like in Goh's research, etc. [10]. The harmonic analyzer has some lacks which are expensive, hard into integrated into the SCADA system, and cannot be used to monitor long distances in real-time [11].…”
Section: Introductionmentioning
confidence: 99%
“…It was indicated that there is a significant relationship between the second harmonic magnitude and the P st value and that IEC flickermeter is not capable of measuring it [16]. This is also a major drawback in the measurement of voltage flicker caused by interharmonics.…”
Section: Introductionmentioning
confidence: 99%